Correlação entre aneuploidia cromossômica em espermatozóides e taxa de implantação embrionária: subtitulo - Santana, Viviane Paiva [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Infertility is directly related to chromosomal abnormalities in germ cells. Among them, the aneuploidies are the most frequent chromosomal abnormalities and responsible for embryo implantation failures, miscarriages, fetal losses and newborns with congenital malformations, mental disability and neuropsychomotor developmental delay. Male patients with normal somatic karyotype may present different rates of aneuploidies in sperm, resulting in abnormal embryos. This study aimed to correlate the frequency of chromosomal aneuploidies in spermatozoa with embryo implantation rate in couples undergoing assisted reproductive techniques. The methodology has included chromosomal analysis by GTG banding and molecular cytogenetic study using Fluorescent In Situ Hybridization technique for evaluation of chromosomes 9, X and Y in germ cells of 22 patients referred to the Human Reproduction Service of the Clinical Hospital FMRP-USP. Embryo implantation rates were determined by hormonal evaluation in maternal peripheral blood and ultrasound confirmation. Two patients presented abnormal karyotype, characterized by polymorphism of the heterochromatic region of the long arm of chromosome 9 and a satellite in the short arm of chromosome 22. Both alterations, usually considered variants of normality, have been related to infertility phenotype and miscarriages. Significant differences were detected between couples who presented pregnancy (group 1) and couples with embryo implantation failure (group 2), with higher frequency of aneusomy and diploidy of chromosome 9, as well as total aneuploidy in sperm of group 2 patients. Our results suggest a correlation between aneuploidy and embryo implantation rates, since the infertile group with reproductive failure has showed higher frequency of aneuploidy. Screening for aneuploidies detection in male germ cells should be included in order to decrease embryo implantation failures, miscarriages and fetuses with chromosomal ...

A etiologia da infertilidade está diretamente relacionada a alterações cromossômicas em células germinativas. Entre elas, as aneuploidias, que se destacam como anormalidades cromossômicas mais frequentes da espécie humana, responsáveis por falhas na implantação embrionária, abortos, perdas fetais e nascidos vivos com síndromes malformativas, deficiência mental e atraso no desenvolvimento neuropsicomotor. Homens com cariótipo somático normal podem apresentar diferentes porcentagens de espermatozóides aneuploides, que após fertilização, geram embriões anômalos. O presente estudo teve por objetivo correlacionar a freqüência de aneuploidias cromossômicas em espermatozóides com a taxa de implantação embrionária de casais submetidos a técnicas de reprodução assistida. A metodologia incluiu análise cromossômica por bandamento GTG para definição do cariótipo somático dos pacientes do sexo masculino e estudo citogenético molecular utilizando a técnica de Hibridação In Situ Fluorescente para detecção de aneussomias dos cromossomos 9, X e Y nas células germinativas masculinas. O grupo amostral foi composto por 22 homens inférteis, atendidos no Serviço de Reprodução Humana do Hospital das Clinicas da FMRP-USP. A taxa de implantação embrionária foi determinada por avaliação hormonal em sangue periférico materno e posterior confirmação ultrassonográfica. Foram detectados dois pacientes com alterações cromossômicas, um com polimorfismo da região heterocromática do braço longo do cromossomo 9 (46,XY,9qh+) e no segundo, presença de satélite no braço curto do cromossomo 22 (46,XY,22ps+). Ambas alterações comumente diagnosticadas como variantes de normalidade, já foram relacionadas ao fenótipo de infertilidade e à ocorrência de abortamentos. Foram encontradas diferenças significativas entre casais que obtiveram gestação (grupo 1) ou falha de implantação embrionária (grupo 2), com maior ...
Keywords: Aneuploidia; Transferência de embrião humano; Cromossomos humanos - Anomalias; Tecnologia da reprodução humana; Espermatozoides; Aneuploidy